Analisis Faktor-Faktor Yang Mempengaruhi Opini Audit Going Concern Pada Perusahaan Pariwisata Dan Transportasi Logistik Di BEI - Nurul Dwi Aprilia; Nur Fitriyah (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2025)
This study aims to analyze the factors that affect the audit opinion of going concern in tourism and logistics transportation sector companies listed on the Indonesia Stock Exchange during the 2019–2023 period. Using a quantitative approach with logistic regression analysis of 100 observations from 20 companies, this study examined the influence of the previous year's audit opinion, financial distress, company size, and company growth. The results showed that the previous year's audit opinion had a significant influence on the audit opinion going concern, while financial distress, company size, and company growth did not show a significant influence. The conclusion of this study confirms that auditors need to consider previous audit opinions in assessing the company's business viability, as well as provide investors with insight into the risks that may be faced by companies in the tourism and transportation logistics sectors. Keywords: Audit Opinion Going Concern; the previous year's audit; Financial Distress; Company Size; Company Growth